Development of Online Thematic Teaching Materials Based on High Order Thinking Skills (HOTS) Subtema Wealth of Energy Sources in Indonesia - Andrajati, Nur Hidayati; Anis, Moh Badiul; Mahmudi, Ali (UIN Fatmawati Sukarno Bengkulu, 2020)
This study aims to describe the actual field conditions regarding the use of existing thematic teaching materials, the need for the development of thematic teaching materials, to get the form of thematic teaching material development and to determine the effectiveness of developing HOTS-based thematic teaching materials on students' creative thinking abilities. The method of this research is Research and Development (R&D) with research subjects of class IV students at MIN 4 and MIN 7 districts of Magelang. The stages of R&D use the ADDIE development procedure. Data collection using interview and questionnaire techniques. The results of this study are as follows: 1) Field conditions have not yet been found on HOTS-based online thematic teaching materials, 2) HOTS-based online thematic teaching materials are needed by teachers in their learning, 3) Teaching materials that have been developed are suitable for testing in learning, 4) Results test the effectiveness of the use of thematic teaching materials with the Wilcocon test obtained a difference of 23.64 meaning an increase in pastest scores against pretest. Standard deviation 4.63 an increase in all students, obtained a value of Z = -5,185 and p-value = 0,000 t 4,788 then with these results it can be concluded that the development of HOTSbased online thematic teaching materials effectively increases the ability to think creatively.